2016
DOI: 10.1590/0104-1428.1920
|View full text |Cite
|
Sign up to set email alerts
|

Investigação do efeito do tempo de exposição à temperatura ambiente e ao tempo de estocagem de um filme adesivo estrutural de resina epoxídica

Abstract: ResumoA exposição de filmes adesivos de resina epoxídica à temperatura ambiente propicia condições que afetam diretamente suas propriedades físicas. Para o adesivo estrutural AF191, de aplicação no setor aeronáutico, isto pode ser confirmado pela súbita perda de pegajosidade ("tack"). Sendo assim, o comportamento do sistema de resina escolhido foi estudado experimentalmente, expondo-se este ao ambiente de laboratório a intervalos pré-determinados de tempo e a diferentes períodos de armazenamento (-18°C). O efe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Moreover, Xia et al [27] observed that the lower the volatile content, the higher the rate of use of the system, since the number of voids contained within the material is reduced, which causes an increase in properties in composites. The prepreg in question had five days of freezer cooling, and although this study does not consider the storage time, it is possible that some of the volatile loss occurred during this time, since the storage time influences the volatile content in the material [28].…”
Section: Gel Time Water Absorption and Volatiles Content Of The Prepregsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Xia et al [27] observed that the lower the volatile content, the higher the rate of use of the system, since the number of voids contained within the material is reduced, which causes an increase in properties in composites. The prepreg in question had five days of freezer cooling, and although this study does not consider the storage time, it is possible that some of the volatile loss occurred during this time, since the storage time influences the volatile content in the material [28].…”
Section: Gel Time Water Absorption and Volatiles Content Of The Prepregsmentioning
confidence: 99%
“…It was observed that the NaOH-treated sisal/epoxy prepreg showed a high adherence capacity, since the material is capable of adhering to itself and to surfaces. According to Silva et al [28], this material is qualified as Level V (high adhesion, glue on gloves, adheres to itself and other surface). As it is a complex phenomenon, it is not possible to decompose the adhesion properties into a single value.…”
Section: Drapeability and Tack Test For The Prepregsmentioning
confidence: 99%